A Longitudinal Study of Sexual Function in Women With Newly Diagnosed Inflammatory Bowel Disease. Issue 7 (6th February 2019) - Shmidt, Eugenia; Suárez-Fariñas, Mayte; Mallette, Meaghan; Moniz, Heather; Bright, Renee; Shah, Samir A; Merrick, Marjorie; Shapiro, Jason; Xu, Fang; Sands, Bruce; Saha, Sumona
ABSTRACT: Background: The literature provides conflicting data on sexual function in women with inflammatory bowel disease (IBD). We aim to describe sexual function at baseline and over time in a prospective inception cohort of adult women with IBD. Methods: Women age 18 years or older enrolled in the Ocean State Crohn's & Colitis Area Registry (OSCCAR) with 2 years of prospective follow-up were included in the study. All subjects were enrolled within 1 year of IBD diagnosis. Female sexual function was assessed using the Female Sexual Function Index (FSFI). Linear mixed effects models were used to assess changes in FSFI by various demographic and clinical factors. Results: One hundred sixteen of 130 eligible women (89%) were included in the study. Ninety-seven percent of women had sexual dysfunction, defined as an FSFI score of <26.55, with a baseline mean FSFI score (SD) of 16.4 (8.4) overall (15.5 [8.6] in Crohn's disease, 17.4 [8.1] in UC, P = 0.22). Despite improvement in overall disease activity, there was no significant change in the FSFI score or individual domain scores over the entire 2-year study period. Among all women with IBD, older age, nonsingle marital status, lower Short Form Health Survey (SF-36) Physical Component Summary score, and the use of biologics were independent risk factors for sexual dysfunction. Conclusions: Almost all women experienced sexual dysfunction that did not improve over time despite improvement in overall disease activity. Future studies are warranted to identify underlying mechanisms that explain the associations between demographic and clinical factors and sexual dysfunction among newly diagnosed women. Video Abstract: